2006
DOI: 10.1002/cvde.200506408
|View full text |Cite
|
Sign up to set email alerts
|

Fast Rate Growth of Organized Carbon Nanotubes by CVD Using Iron Pentacarbonyl as Gas‐Phase Catalyst

Abstract: Organized carbon nanotubes (CNTs) have been grown at a fast rate by a gas-phase, catalytic CVD technique at 600-750°C for 15 min with the iron pentacarbonyl/acetylene/hydrogen system. The CNT growth at various temperatures and flow rates of iron pentacarbonyl, acetylene, and hydrogen, has been quantitatively analyzed by its length. The CNT growth accelerates with growth temperatures up to 700°C, but depends upon growth conditions at 750°C. Acetylene at a higher input deactivates catalysts owing to its supersat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…While for CVD method, the length of CNTs can achieve 850 mm [16]. Thus, the length of CNTs in this research is not so long as that of CVD method.…”
Section: Structure Of Cnts and Field Emission Testmentioning
confidence: 90%
“…While for CVD method, the length of CNTs can achieve 850 mm [16]. Thus, the length of CNTs in this research is not so long as that of CVD method.…”
Section: Structure Of Cnts and Field Emission Testmentioning
confidence: 90%
“…In the unsupported catalyst approach, a volatile compound containing the catalytic element [115,116], e.g., Fe (CO) 5 , Fe(C 5 H 5 ) 2 , or Ni(C 5 H 5 ) 2 is used as the catalyst source. The nanotubes form in the vapor phase and condense onto cold surfaces.…”
Section: Catalyst Typementioning
confidence: 99%
“…This one-step CCVD processes enables the constant renewing of the catalyst particles as reported at high temperature (850 °C) by Castro et al [ 40 ]. However, in the literature, very few studies of VACNT synthesis with a single-step method are reported at a low temperature and atmospheric pressure [ 27 , 39 , 41 , 42 , 43 , 44 ]. Unlike two-step processes, here we can assume that particle deactivation will be limited.…”
Section: Introductionmentioning
confidence: 99%